FMS-Related Tyrosine Kinase 3 Ligand Promotes Radioresistance in Esophageal Squamous Cell Carcinoma - Zhu, Zuoquan; Song, Jiahang; Gu, Junjie; Xu, Bing; Sun, Xinchen; Zhang, Shu (Frontiers in Pharmacology, 2021)
Aim: The FMS-related tyrosine kinase 3 ligand (FL) has an important role in regulating FMS-related tyrosine kinase 3 (Flt-3) activity. Serum FL levels are markedly increased among patients with hematopoietic disease. However, its role in radiation treatment remains unclear. In this study, we investigated the effects of FL on radiotherapy for esophageal squamous cell carcinoma (ESCC). Methods: KYSE150 and KYSE450 cells were stimulated with FL (200 ng/mL). mRNA expression was analyzed using qRT-PCR. Cell viability was checked using CCK-8 assay kits. Proliferation was determined using the EdU assay. Radiosensitivity was detected through a colony-forming assay. Flow cytometry was used to evaluate cell apoptosis. The number of γH2AX foci was verified using an immunofluorescence assay. The change in relative proteins was determined by western blot analysis. The growth of transplanted tumors was demonstrated in nude mice. Results: Our results showed that FL increased the radiation resistance of ESCC cells by promoting clone formation, increasing EdU incorporation, enhancing DNA damage repair, and inhibiting apoptosis. Moreover, the Flt-3 receptor expression significantly increased in ESCC cells after radiation, which may have been an important factor in their radioresistance. Conclusions: Our results suggest that FL increases the radioresistance of esophageal cancer cells and that FL-Flt-3 could be a potential target for enhancing radiosensitivity in ESCC.